2019
DOI: 10.1017/s0950268819002024
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the real burden of invasive meningococcal disease in Argentina

Abstract: Among the different existing types of bacterial meningitis, the one caused by Neisseria meningitidis is the main presentation of invasive meningococcal disease (IMD). IMD is a significant public health concern and has a reported incidence rate in Argentina of 0.44 cases per 100 000 inhabitants in 2015. However, the actual incidence is thought to be higher as passive surveillance systems neither report nor identify 100% of all cases. The aim of this study is to develop an estimation of the burden of IMD in Arge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…This may be due to incomplete reporting and may include misdiagnoses, leading to underestimation of the true burden of IMD. 34 , 35 As such, compulsory surveillance or laboratory-based reporting is preferred. Further, access to molecular-based methodologies, such as polymerase chain reaction (PCR) and whole genome sequencing (WGS), is vital to not only to improve diagnostic accuracy and allow timely treatment, but also to inform future vaccination strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to incomplete reporting and may include misdiagnoses, leading to underestimation of the true burden of IMD. 34 , 35 As such, compulsory surveillance or laboratory-based reporting is preferred. Further, access to molecular-based methodologies, such as polymerase chain reaction (PCR) and whole genome sequencing (WGS), is vital to not only to improve diagnostic accuracy and allow timely treatment, but also to inform future vaccination strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 A decrease in MenW cases was also in reported in Argentina, although the incidence was reported to decrease two years prior to the implementation of routine vaccination. 27 During the COVID-19 pandemic, non-pharmacological intervention measures were implemented in March 2020, which were associated with reduction of many infectious diseases. 28 , 29 , 30 Potentially, a rebound of (meningococcal) meningitis may occur in the Netherlands, as resurgence of respiratory infections has occurred after relaxation of restriction measures against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests there was under-reporting, despite the clinical severity of the disease. Other authors have also found under-reporting of this disease 40. It is very important to improve reporting by all physicians and microbiologists to the SDR and MRS to assess the impact of interventions such as immunisation.…”
Section: Discussionmentioning
confidence: 99%